PENGARUH SELF EFFICACY TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA PESERTA DIDIK SMP: The Influence Of Self Efficacy On The Mathematical Problem Solving Ability Of Junior High School Students - Nurwahda, Nurwahda; Nursupiamin, Nursupiamin; Badjeber, Rafiq (Aksioma, 2023)
The purpose of this study was to determine the effect of self-efficacy on the math problem solving abilities of junior high school students. The method used in this research is quantitative with ex post facto design. The population in this study were all students of class VIII SMP Negeri 3 Palu. The sample studied was 174 students who were obtained using simple random sampling technique. The instruments in this study used a self-efficacy questionnaire and a math problem-solving ability test. The results of the study showed that there was an effect of self-efficacy on students' mathematical problem-solving skills at SMP Negeri 3 Palu. The influence of self-efficacy on the ability to solve mathematical problems is 27.2%.